Withholding life prolonging treatment, and self deception. Issue 6 (1st December 2002) - Sayers, G M; Perera, S
Abstract : Objectives: To compare non-treatment decision making by general practitioners and geriatricians in response to vignettes. To see whether the doctors' decisions were informed by ethical or legal reasoning. Design: Qualitative study in which consultant geriatricians and general practitioners (GPs) randomly selected from a list of local practitioners were interviewed. The doctors were asked whether patients described in five vignettes should be admitted to hospital for further care, and to give supporting reasons. They were asked with whom they would consult, who they believed ought to make such decisions, and whether the relatives' preferences would influence their decision making. Main measures: To analyse the factors influencing the doctors' decisions not to admit otherwise terminally ill patients to hospital for life prolonging treatment. Results: Seventeen GPs and 18 geriatricians completed the interview. All vignettes produced strong concordance in decision making between both groups. Ten per cent of the doctors would provide life prolonging treatment to patients with severe brain damage. Most would admit a surgical patient regardless of age or disability. Medical reasons were largely used to explain decision making. The wishes of relatives were influential and resource considerations were not. There was variability regarding decision making responsibility. Conclusions: Little attempt was made to link decision making with ethical or legal concepts and there may have been non-recognition, or denial, of the ethical consequences of failure to admit. The process of decision making may involve deception. This may be conscious, because of the illegality of euthanasia, or unconscious (self deception), because of deepseated medical and societal reluctance to accept that intentionally withholding life prolonging treatment may equate with intentionally causing death.